High space resolution µ-RWELL for high rate applications. (April 2020) - Bencivenni, G.; Felici, G.; Gatta, M.; Giovannetti, M.; Morello, G.; Poli Lener, M.; de Oliveira, R.; Ochi, A.; Tskhadadze, E.
Abstract: The µ-RWELL is a single-amplification stage resisitive MPGD. The amplification element, realized on a polyimide foil micro-patterned with a high density blind-holes (wells), is embedded through a thin resistive film, in the readout PCB. The introduction of the resistive layer affects the charge spread on the readout electrodes and suppresses the transition from streamer to spark giving the possibility to achieve large gains (>10 4 ). As a drawback the capability to stand high particle fluxes is reduced. In order to get rid of such a limitation different resistive layouts with prompt current evacuation schemes have been designed. In this work we present the study of the performance of the high rate layouts done at PSI, together with the measurement of the space resolution for orthogonal and inclined tracks performed at CERN.